Agents and data mining interaction : 10th International Workshop, ADMI 2014, Paris, France, May 5-9, 2014, Revised selected papers /: 10th International Workshop, ADMI 2014, Paris, France, May 5-9, 2014, Revised selected papers. (2015) - Unknown
No abstract available